Syria : the fall of the house of Assad - Lesch, David W. (Yale University Press, 2012)
Amidst the bombings, shootings, political turmoil, and mass exodus in Syria, it's difficult to follow the trajectory of its recent troubled history. One can start in 2000, when Syrian President Bashar al-Assad came to power. David W. Lesch, author of Syria: The Fall of the House of Assad, can trace this path because he knew President Assad personally, perhaps better than anyone else in the West. Lesch's book at first highlights the humanity and promise once shown in President Assad. Later, it is filled with disappointment. He explains that Assad was never meant to rule, and it was only after the untimely death of his brother that the role was thrust upon him. Assad was an ophthalmologist, with a wife and a good family. But it did not take long for the power to corrupt him. Lesch is far from an impartial author. Having known Assad for years, through a series of meetings as a researcher and consultant, Lesch does not hide his regret at the turn of events. In this timely book, the author explores Assad's failed leadership, his transformation from bearer of hope to reactionary tyrant, and his regime's violent response to the uprising of his people in the wake of the Arab Spring. - Publisher.